Studying Natural Science in Elementary School Using NOS-Oriented Cooperative Learning Model with the NHT Type (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2018)
Elementary school students’ achievement in natural science in the academic year of 2015/2016 at Cluster V, Buleleng regency, Bali province was considerably low. An early observation also revealed low motivation, negative attitudes towards teachers, low self-esteem and low confidence in self-capability. Therefore, a breakthrough approach was urgently required to improve the students' performance in natural science learning. The current article aimed at investigating the effects of the (Nature of Science) NOS-oriented cooperative learning model with the Numbered Head Together (NHT) on the elementary school students’ achievement in natural science. The study was a quasi-experimental research adopting the post-test only control group design. The research conducted in elementary schools in Cluster V Buleleng sub-district, Buleleng regency, Bali, Indonesia. The research subject was 137 students in Grade 5 consisting of six classes from 5 elementary schools. The hypothesis was examined using an inferential statistics, the t-test. The results showed that there was a significant difference in the learning results of natural science between the students taught with the NOS-oriented cooperative learning model with the NHT type and those with the conventional learning model (t count = 7,048 t table = 2,000). The students taught with the NOS-oriented constructive learning model with the NHT type achieved better than those with the conventional learning model. Therefore, it concluded that the NOS-oriented cooperative learning model with the NHT type gave positive effects on the fifth year students’ achievement in natural science learning.